Exceeding expectations : service tips and techniques to keep your customers coming back - 4 0 16; Culinary Institute of America; 5 ([Hyde Park, N.Y.] : Culinary Institute of America, 2007)
Every foodservice professional--from the beginner to the most accomplished chef--needs a comprehensive foundation of knowledge and skills to have the best opportunity for success. The Culinary Institute of America is the authority for providing the knowledge needed to educate, reinforce, and verify today's skills, techniques, and procedures -- container. Presenter describes quality service as hospitable, courteous, well-timed, consistent, efficient, knowledgeable,and communicating efficiently with the customers.
Title on DVD: Exceeding expectations.;ProChef Training Materials -- above title on disc cover and on container.
Editors, Philip Miller, Skip Thela, Maria Renz.
Enhanced DVD; includes Adobe Acrobat file with forms and information. System requirements for DVD-ROM features: Computer with Windows and a DVD-ROM drive..
Closed-captioned.
Keywords: 2 -- 0; 6; Quality control.;Quality control.;Employees;Training of. -- Food service;Table service;Food service employees.;Food service management.;Restaurants;Films for the hearing impaired. -- 20; 20; 2